A cyclic symmetric model for the investigation of vibration reduction of hard-coating blisk. Issue 9 (22nd May 2020) - Sun, Wei; Yang, Shuai; Gao, Junnan; Yan, Xianfei
Abstract : Purpose: It is very important to create a useful cyclic symmetric model for the investigation of the vibration reduction effect of hard-coating blisk. This study aims to develop a cyclic symmetry algorithm which can determine the mode of blisk in the sector coordinate system directly. Design/methodology/approach: Using the exponential and real quasi-equivalent Fourier matrices, the formulas for solving the sector mode were derived, and the relationship between the two kinds of sector modes was also discussed. Based on the proposed cyclic symmetry algorithm, the vibration characteristics of an academic blisk were solved, and the formulas for solving the natural characteristics and vibration responses of the coated blisk were given. Findings: A blisk with NiCrAlCoY+YSZ hard coating on both sides of each blade was chosen as a case to demonstrate the presented method. Based on the verification analysis model, the influences of coating thickness on the vibration reduction effect of the blisk were discussed. The results show that the hard coating has good vibration reduction effect on the blisk even the coating thickness is very thin and the vibration reduction effect of hard coating in the high frequency range is obviously better than that in the low frequency range. Originality/value: As a large number of reduced order modeling methods of blisk are implemented based on the sector modes, the proposed method which can obtain the sector modes directly will significantly improve the efficiency of dynamic modeling and analysis of the coated blisk structure.